A new understanding of 'New Media': Online platforms as digital mediums. (April 2020) - McMullan, John
For the last few decades, media theorists have been faced with the understanding that the networked digital computer is the meta-medium to end all mediums. This places researchers in the curious position where online platforms, such as YouTube, cannot legitimately and directly be contrasted with traditional analogue mediums, such as cinema and television. To address this inconsistency, I developed the theory of foundation technologies and their respective proto-affordances, which demonstrates the existence of past periods of 'new media'. These were brought about by the introduction of key technologies that each offered, at the time, a new and unique underlying affordance to a society. Each new 'proto-affordance' inspired social disruption, as new specific mediums were spawned – each remediating existing mediums of similar mode. This framework shows digitality as another evolutionary step in a line of foundation technologies, which includes the artefact, the machine and electricity. The theory of foundation technologies permits software-based online platforms, such as YouTube, SoundCloud and Twitter, to be called digital mediums, and thus aids in understanding their technological substrate and unique affordances. Justifying this relation between old mediums and new, digital, ones equips us to more effectively comprehend and analyse these platforms as to their social adoption and uses, cultural practices, implications and effects. This allows us to better understand and control our present, and even guide our potential future.